2018
DOI: 10.1007/s10461-018-2066-9
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Quality Assurance Initiatives and Workplace Policies and Procedures on HIV/AIDS-Related Stigma Experienced by Patients and Nurses in Regions with High Prevalence of HIV/AIDS

Abstract: Stigma is commonly experienced by people living with HIV/AIDS and by those providing care to HIV/AIDS patients. Few intervention studies have explored the impact of workplace policies and/or quality improvement on stigma. We examine the contribution of health care workplace policies, procedures and quality assurance initiatives, and self- and peer-assessed individual nurse practices, to nurse-reported HIV/AIDS-stigma practices toward patients living with HIV/AIDS and nurses in health care settings. Our sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
3
5
0
3
Order By: Relevance
“…Results of the study revealed that PLWHA significantly experience more enacted HIV and AIDS stigma over other stigma dimensions relative to PLWHPT. This finding is consistent with other previous studies, where PLWHA reported higher incidence rates of stigma experiences relative to people with other chronic conditions (Blake et al 2017 ; dos Santos et al 2014 ; Hewko et al 2018 ; Idemudia & Matemela 2012 ; Mak et al 2007 ). This finding perhaps might not have been anticipated, considering the vigorous global state of the HIV and AIDS educational programmes that have already been put in place with the rationale of combating stigma.…”
Section: Discussionsupporting
confidence: 92%
“…Results of the study revealed that PLWHA significantly experience more enacted HIV and AIDS stigma over other stigma dimensions relative to PLWHPT. This finding is consistent with other previous studies, where PLWHA reported higher incidence rates of stigma experiences relative to people with other chronic conditions (Blake et al 2017 ; dos Santos et al 2014 ; Hewko et al 2018 ; Idemudia & Matemela 2012 ; Mak et al 2007 ). This finding perhaps might not have been anticipated, considering the vigorous global state of the HIV and AIDS educational programmes that have already been put in place with the rationale of combating stigma.…”
Section: Discussionsupporting
confidence: 92%
“…To be effective, S&D interventions that target individual attitudes and behaviours must also consider the prevailing processes within healthcare organisations, and how these processes mediate the translation of knowledge gains into outcomes such as reductions in S&D and changes in organisational practice. Unfortunately, few studies to date have explored the effectiveness of organisation-level interventions in reducing S&D,13 14 and little work has been done to translate aspirations of health equity into institutional practice.…”
Section: Introductionmentioning
confidence: 99%
“…Application of quality improvement (QI) methods offers an innovative approach to identify individual-level and system-level root causes of S&D and mount data-driven, team-based, contextually appropriate responses to address them in a local setting. QI approaches have long been applied to address gaps in HIV clinical outcomes such as care engagement and viral suppression,16 yet little work to date has sought to apply these approaches to S&D reduction 14. As national HIV programme monitors the quality of HIV care as part of routine activities, the incorporation of S&D measurement and intervention into these activities may represent a sustainable means to rapidly scale S&D-reduction programming.…”
Section: Introductionmentioning
confidence: 99%
“…Вивчення літератури з цієї проблеми показало тенденцію до суттєвого зростання обсягу публікацій за останнє десятиліття щодо рівня ЯЖ серед ЛЖВ [8,9,10]. Найбільша кількість публікацій фіксується в роботах стосовно ЯЖ ЛЖВ в країнах Африки, особливо на південь від Сахари, в країнах Карибського басейну, Центральної Азії, Південної Америки а також Європи [8,9,11,12]. В цих публікаціях висвітлюються питання впливу на ЯЖ ЛЖВ соціально-економічних умов та доступ до медичних послуг, етнічні, релігійні та культурні особливості [13].…”
unclassified
“…Також порівнюючи пацієнтів жіночої та чоловічої статі, виявлено що у двох дослідних групах загальний показник ЯЖ був нижчим у жінок, а саме у першій групі 42,7±4,23 (p<0,05) у жінок і 49,7±2,54 (p<0,05) у чоловіків, а у другій групі − 38,5±1,43 та 40,3±1,74 відповідно (p<0,05). Аналогічні результати були у іноземних дослідників [8,9,10,17].…”
unclassified